2016
DOI: 10.1098/rspb.2016.0376
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkeys show human-like changes in gaze following across the lifespan

Abstract: Gaze following, or co-orienting with others, is a foundational skill for human social behaviour. The emergence of this capacity scaffolds critical humanspecific abilities such as theory of mind and language. Non-human primates also follow others' gaze, but less is known about how the cognitive mechanisms supporting this behaviour develop over the lifespan. Here we experimentally tested gaze following in 481 semi-free-ranging rhesus macaques (Macaca mulatta) ranging from infancy to old age. We found that monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 66 publications
6
52
0
Order By: Relevance
“…In fact, sex differences in sociality are widespread not only among humans, but throughout mammals, indicating possible evolutionary roots (Christov-Moore et al 2014). Furthermore, a recent study of a large sample of rhesus macaques ( n =481) reported female macaques were more likely to gaze-follow than males (Rosati et al 2016), consistent with our findings. Interestingly, these sex differences were evident across a wide variety of ages, from infancy through adulthood, and grew larger with age, paralleling findings in humans (e.g., Bayliss et al, 2005; Deaner et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, sex differences in sociality are widespread not only among humans, but throughout mammals, indicating possible evolutionary roots (Christov-Moore et al 2014). Furthermore, a recent study of a large sample of rhesus macaques ( n =481) reported female macaques were more likely to gaze-follow than males (Rosati et al 2016), consistent with our findings. Interestingly, these sex differences were evident across a wide variety of ages, from infancy through adulthood, and grew larger with age, paralleling findings in humans (e.g., Bayliss et al, 2005; Deaner et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…1. Rhesus data were partially reported in previous work (see Study 2 in Rosati et al, 2016). Both populations are semi-free-ranging and highly habituated to humans.…”
Section: Methodsmentioning
confidence: 64%
“…The demonstrator, experimenter 1 (E1), first attracted the monkey’s attention to her face (by calling ‘monkey’ and/or clapping her hands). When the monkey was looking, E1 said ‘now’ and then looked straight up or down, rotating her entire head with her eyes open for 10 s (following the same procedure in Rosati et al (2016) (see Supplementary Material 1, Fig. S1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations